Pengaruh Good Corporate Governance, Moralitas Individu, dan Personal Culture Terhadap Pencegahan Kecurangan Pada Lembaga Perkreditan Desa (LPD) Se - Kecamatan Tejakulaa - Komang Riska Pratiwi; Made Arie Wahyuni (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to determine the effect of good corporate governance, individual morality, and personal culture on fraud prevention in LPD Se – Tejakula District. This research is quantitative research. The sample used is as many as 95 with a sampling technique that is saturated sampling. In this study, the data used were primary data, namely a questionnaire which was measured using SPSS. The results of this study indicate that (1) good corporate governance has a positive and significant effect on fraud prevention, (2) individual morality has a positive and significant effect on fraud prevention, (3) personal culture has a positive effect on fraud prevention